Hubungan Pengetahuan dan Sikap dengan Perilaku Buang Air Besar Sembarangan (BABS) - Desi Mustika Wati; Yuanita Windusari; Nur Alam Fajar (SENTRI: Jurnal Riset Ilmiah, 2025)
Open defecation remains a significant public health problem in Indonesia despite various intervention programs implemented. Knowledge and attitudes are predisposing factors suspected to influence open defecation behavior, but there are still inconsistencies in research findings regarding the strength of their relationship with open defecation behavior. This study aims to analyze the relationship between knowledge and attitudes with open defecation behavior and identify which factor has the strongest relationship. This study used a qualitative approach with a literature review method on ten research articles published from 2021-2025. Literature search was conducted on academic databases using keywords "open defecation", "BABS", "knowledge", "attitude", and "behavior". Data analysis was performed using thematic analysis techniques to identify patterns of relationships between the variables studied. The review results showed inconsistent findings regarding the relationship between knowledge and open defecation behavior, with four studies reporting no significant relationship (p>0.05) and six studies finding significant relationships (p<0.05). In contrast, attitude showed a more consistent relationship with open defecation behavior, where eight out of ten studies reported significant relationships with odds ratio values ranging from 4.5-10.788. Conclusion: Attitude has a stronger and more consistent relationship compared to knowledge in shaping open defecation behavior, therefore behavior change interventions need to place greater emphasis on forming positive attitudes toward sanitation.